Strut and tie model optimization for reinforced concrete bridge pier head structure using a genetic algorithm - Bambang Piscesa; Tavio Tavio (Journal of Civil Engineering, 2020)
Strut and tie model (STM) is more suitable to design the pierhead structures which resist high shear forces transferred from the girders. These pierhead structures behave like the disturbed regions as in reinforced concrete deep beam. The design of the struts and ties elements requires the initial geometry configuration of the truss model where its boundaries are limited by the shape of the pier head structures. To find the optimum topological shape of the truss model, the genetic algorithm (GA) optimization technique is used in this paper. The objective functions in the GA optimization consisted of minimizing the usage of concrete and steel reinforcement material and ensuring all the stress ratio of the strut and tie elements are less than equal to unity. Both prestressed and non-prestressed pierheads are investigated in this paper. The use of prestressing in the pierhead structures reduces the stresses in the main tension tie significantly and allowing some members of the shear tie and compression struts to have almost zero stresses. For these elements with zero stresses, the elements can be removed and reduces the concrete and rebar materials usage. Furthermore, the genetic algorithm optimization is found to be successful to ensure all the stress ratio in the members to be less than equal to unity.